2021
DOI: 10.1021/acs.jpca.1c02132
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for the Formation of Formamide, a Prebiotic Biomonomer: Metal-Ions in Interstellar Gas-Phase Chemistry

Abstract: The chemistry occurring in the interstellar medium (ISM) is an active area of contemporary research. New aspects of interstellar chemistry are getting unraveled regularly. In this context, the role of metal-ions in the chemistry occurring in the ISM is not well-studied so far. Herein, we highlight the role of metal-ions in interstellar chemistry. For this purpose, we choose the problem of gas-phase formamide formation in interstellar molecular clouds. Formamide is a key biomonomer and contains the simplest pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 104 publications
2
20
0
Order By: Relevance
“…In this section, we shall first present our computational results for the interstellar formation of ethylene oxide, followed by that of propylene oxide. Throughout, consistent with our protocol followed in earlier works, , subsequent analysis is based on zero-point corrected quantum chemical energies and not free-energies. This is done to avoid any assumption based on the prevalence of Boltzmann distributions, which may not always be valid in all parts of the ISM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we shall first present our computational results for the interstellar formation of ethylene oxide, followed by that of propylene oxide. Throughout, consistent with our protocol followed in earlier works, , subsequent analysis is based on zero-point corrected quantum chemical energies and not free-energies. This is done to avoid any assumption based on the prevalence of Boltzmann distributions, which may not always be valid in all parts of the ISM.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, we did not consider the chemistry of other main group elements such as Na + , K + in this work, given the nature of the barriers, when they were proposed to mediate the formation of other iCOMs . However, just as Woon has rightly pointed out very recently, we opine that a huge trove of new chemistry in the ISM is expected to come out by investigating the role of metal-ion mediated generation of iCOMs in the ISM including both main-group as well as transition metals. Interstellar prochirality and chirality: Propylene is a prochiral molecule.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…More than half a decade passed between the discovery of a new but unknown radical species in 1986 by Cernicharo et al and the experimental work of Kawaguchi et al and supporting theoretical work of Ishii et al which demonstrated that the unidentified molecule was MgNC. In addition to the further detections of Mg-containing compounds enumerated previously, various experimental, theoretical, and modeling studies have appeared in the following next three decades. Work continues, with recent theoretical efforts to characterize magnesacylopropane, c-MgC 2 H 2 , and to elucidate gas phase routes to formamide mediated by Mg + , Mg 2+ , and other metal ions . However, all of the cited prior efforts focused exclusively on gas phase processes.…”
Section: Introductionmentioning
confidence: 99%
“…33−60 Work continues, with recent theoretical efforts to characterize magnesacylopropane, 60 c-MgC 2 H 2 , and to elucidate gas phase routes to formamide mediated by Mg + , Mg 2+ , and other metal ions. 58 However, all of the cited prior efforts focused exclusively on gas phase processes. In the present work, the chemistry of MgNC adsorbed onto an ice surface is explored.…”
Section: ■ Introductionmentioning
confidence: 99%